Pemberdayaan OSAMU dan Poskestren dalam Pencegahan Penyakit Skabies: Pendekatan Kognitif dengan Moddeling Media Video Santri Almuawanah Cinangka Rajadesa - Lilis Lismayanti; Maulana Sidiq; Isyeu Sriagutini; Ade fitriani; Ana Hertiana Muzdalipah; Della Yuniasih (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Scabies is an infectious skin disease caused by Sarcopes Scabei. Scabies. This service aims to increase the knowledge and awareness of students at Al-Mu'aawanah Islamic Boarding School regarding the prevention of scabies through the empowerment of the Al-Mu'aawanah Santri Organization (OSAMU) and the Pesantren Health Post (Poskestren) with a cognitive approach using video media. Methods: the service used was health counseling which was attended by 65 respondents. The results showed a significant increase in santri knowledge related to the prevention of scabies, from 38.5% before intervention to 92.3% after counseling. Counseling using video media proved to be more interesting and effective in increasing knowledge than conventional methods.